Spatiotemporal characteristics of air pollution in Chengdu-Chongqing urban agglomeration (CCUA) in Southwest, China: 2015–2021. (1st January 2023) - Tan, Shaojun; Xie, Deti; Ni, Chengsheng; Zhao, Guangyao; Shao, Jingan; Chen, Fangxin; Ni, Jiupai
Abstract: Studying the spatiotemporal characteristics of air pollutants in urban agglomerations and their response factors will help to improve the quality of urban living. In combining air quality monitoring data and wavelet analysis from the Chengdu-Chongqing urban agglomeration (CCUA), this study assessed the spatiotemporal distribution characteristics and influential factors of air pollutants on daily, monthly and annual scales. The results showed that the concentration of air pollutants in the CCUA has decreased year by year, and air quality has improved. Except for O3, pollutants in autumn and winter were higher than those in summer. The spatial distribution of air pollutants was obvious distributed in Chengdu, Chongqing, Zigong and Dazhou. Pollution incidents were mainly concentrated in winter. The 6 air pollutants and air quality index (AQI) have dominant periods on multiple time scales. AQI showed positive coherence with PM2.5 and PM10 on multiple time scales, and obvious positive coherence with SO2, CO, NO2 and O3 in the short term scale. AQI was not strongly correlated with the fire point, but exhibited obvious negative coherence in the long term scale. In addition, AQI showed an obvious positive correlation with temperature and sunshine hours in short term, and a clear negative correlation with humidity and rainfall. The research results of this paper will provide a reference for pollution prevention and control in the CCUA. Highlights: Wavelet and IDW used to analysis air pollutants spatiotemporal characteristics. Air pollutants shows obvious periodicity and mutation. There is a certain correlation between AQI and wild burning sites. Rainfall and humidity have a scrubbing effect on air pollutants. The research results can provide policy basis to improve air quality in region.